The Impact of External Communication Strategy on Blockchain Startups: Analysing the Case of Credits Blockchain Platform - Bruce, Sadia (International Journal of Applied Research in Management and Economics, 2021)
Communication is always an important part of establishing a business’ sense of direction and growth; information needs to be accessed by the receiver in an appropriate way and put across in a clear, impactful and engaging way so that it will have an effect on the user. This research paper gives a detailed review of external communication strategies in the blockchain industry and how startups could revise their strategies over time to build trust and reputation. Even if the blockchain industry is becoming the preferred choice for businesses to securely conduct transactions, not many blockchain projects find acceptance amongst investors. Blockchain projects focus on raising funds for their ventures at a stage where they seldom have a viable product and using unregulated means of fundraising like initial coin offerings (ICO) or initial exchange offerings (IEO) have in turn been used to accumulate capital for such projects. With trust depleting in these means of fundraising, blockchain are becoming increasingly aware of the need to tailor their communication with potential investors. In this study, we’ve conducted cross-sectional studies across two separate times, once in 2017-18 at the time ICOs found prominence and then later in 2021, exploring how external communication strategies were revised and improved upon over time to ensure success and favour amongst users and investors.